Peran Keluarga Untuk Menciptakan Lingkungan Belajar Di Rumah: Perspektif Pendidikan Agama Hindu - Ketut Bali Sastrawan (Jurnal Penelitian Agama Hindu, 2021)
The Covid-19 pandemic has had a huge impact on the world of education. Government policies that implement learning from home open up public insight about the role of the family in education. This research is a qualitative descriptive research. The role of the family in creating a good learning environment for children is very large. Families, especially parents, play a role in creating a learning environment for children by developing a sense of affection in the family, building communication with children and parents being an example for children. Discipline also needs to be developed in a child. The Hindu community home environment can be a good learning environment for Hindu children if used properly. The architectural patterns of Balinese houses are filled with symbols that have certain meanings in Balinese society. Religious symbols influence the life of Hindu society and create a learning environment for children.